The influence of pedagogic competencies and diverse professional competencies on educator-certified teachers with teachers not yet certified educators. - Ali Yusuf; Yowelna Tarumasely; hadi Suryanto; Yayuk Chayatun Machsunah (Journal of diversity in learning (JDIL), 2021)
This study aims to describe the certification of educators, pedagogic competencies and professional competencies and to measure whether or not there are differences in pedagogic competence and professional competence between teachers certified educators and teachers have not yet certified educators This research includes research surveys with quantitative approaches that use inferential statistical analysis with non-parametric statistical tests that are different tests using rumu Test Mann Whitney. The population and samples in this study are all teachers who are either certified or who have not been certified. The data collection method uses the questionnaire as the primary data and is supported by interviews and documentation as secondary data. The results of the study showed that for pedagogic competencies and professional competencies teachers included good categories, while in the test results U Mann Whitney obtained U Count = 182.5 and U Table = 136. Which means that Ha is accepted and Ho is rejected because the U Count ≥ value rather than U Table means that there are differences in pedagogic competencies and professional competencies between educator-certified teachers and teachers who have not been certified educators, this indicates that educator certification has had an influence on the improvement of pedagogic competencies and professional competencies although not very large.